2018
DOI: 10.1016/j.pedneo.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for nosocomial infections after cardiac surgery in newborns with congenital heart disease

Abstract: Newborns with non-cardiac congenital malformations and with >7 days of mechanical ventilation were at higher risk for a postoperative NI. Efforts must focus on preventable infections, especially in bloodstream catheter-related infections, which account for 20.5% of all NIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…In addition, by increasing enteral feeds, the risks associated with prolonged TPN are avoided. All this should be of benefit to these infants who are at risk of developing postoperative severe bacterial infections 24. As described in a review by Niño et al , multiple randomised clinical trials have now validated the observation that breast milk reduces the incidence of NEC 25.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, by increasing enteral feeds, the risks associated with prolonged TPN are avoided. All this should be of benefit to these infants who are at risk of developing postoperative severe bacterial infections 24. As described in a review by Niño et al , multiple randomised clinical trials have now validated the observation that breast milk reduces the incidence of NEC 25.…”
Section: Discussionmentioning
confidence: 94%
“…Patients experiencing severe bleeding while on ECMO are treated with large doses of RBCs, FFP, and PLTs. Massive transfusions are a known risk factor for infections in cardiac surgery both in pediatric 19 and adult 20 patients. In addition, they have an increased manipulation of the infusion lines and more often require surgical re-explorations, which are again risk factors for infections.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Another retrospective study of 634 CHD patients from the USA reported that 38 patients were diagnosed with HAIs 90 days after surgery, including 19 blood-borne infections (3.0%), 9 operative site infections (1.4%), 6 infective endocarditis (0.95%), and 4 ventilator-related pulmonary infections (0.6%); the total infection rate was 5.99%. [ 11 ] Many studies have confirmed [ 12 – 15 ] that young age, underweight, long operation time, long clamping time, long mechanical ventilation time, and long ICU stay are risk factors for HAIs, but the results were inconsistent to varying degrees in quantitative risk indicator studies. A study in neonates from the USA reported that the risk factors for HAIs also included central venous catheter indwelling time >14 days and >5 postoperative blood transfusions.…”
Section: Discussionmentioning
confidence: 99%